Pengaruh Iklim Organisasi Sekolah, Kompetensi Guru dan Motivasi Kerja terhadap Mutu Sekolah - Sismawati, Eni; Juliejantiningsih, Yovitha; Sudana, I Made (PGRI Kota Semarang, 2024)
Abstract Quality is something that is considered an important part, because quality basically shows the superiority of a product when compared to other products. Likewise, school quality is a very important thing to be paid attention to by the relevant parties for the success of education in Indonesia. It is hoped that good school quality will produce the next generation who are intelligent and have character. The aims of this research are (1) to measure the magnitude of the influence of school organizational climate on school quality (2) to measure the magnitude of the influence of teacher competence on school quality (3) to measure the magnitude of the influence of work motivation on school quality (4) to measure the magnitude of the influence of school organizational climateand teacher competency and work motivation simultaneously on school quality. The population is 6 schools with 158 teachers and a samples size of 110 people. Which was determined by proportionate random sampling, data collection using a questionnaire. Data analysis using descriptive analysis, prerequisite tests, coefficient test, correlation, determinationof single regression analysis and multiple regression analysis calculated using the SPSS for Windows Release 16 program. The result of the research show that the school organizational climate is in the fairly good category, teacher competence is in the good category, work motivation is in the quite good category. From the hypothesis test, it was found that there was a positive influence of school organizational climate on school quality of 4,2%. There is a positive influence of teacher competence on school quality of 12,9%; there is a positive influence of work motivation on school qulity by 20%. There is a positive influence of school organizational climate, teacher competency and work motivation on school quality of 23,9%. Based on the research result, it is recommended that (1) the education office provide direction to school principals regarding their duties as leaders. Teachers and school principals must make effort to improve these conditions. (2) The principal provides opportunities for teachers to take part in training, seminars, workshops related to teacher competency, especially social competency. (3) Teachers must play an active role in creating discipline and pleasant working atmosphere as a positive school organizational climate. Key words: school organizational climate, teacher competency, work motivation, school quality.